Law and policy in modern family finance : property division in the 21st century / edited by Jessica Palmer, Nicola Peart, Margaret Briggs, Mark Henaghan. - Palmer, Jessica; Peart, Nicola; Briggs, Margaret, 1964-; Henaghan, Mark (Intersentia, 2017)
Law and Policy in Modern Family Finance - Property Division in the 21st Century adopts a conceptual approach to address key questions about the legal division of property when a marriage, civil union, de facto relationship, or other close personal relationship ends. These questions include: which relationships should be subject to a statutory regime; which property should be shared; whether property held on trust should be included; how property should be shared; how economic disparity caused by the division of functions within the relationship should be addressed, if at all; whether, and if so to what extent, the interests of children of the relationship should be considered; whether parties should be allowed to contract out of a statutory regime and, if so, whether such contracts should be binding; and whether death should be treated in the same way as relationship break-down. The authors use New Zealand's current legislative framework as a basis for critical analysis and reflection. Despite New Zealand's Property (Relationships) Act 1976 being hailed as socially progressive legislation when it was enacted, there is concern in New Zealand that its property sharing regime no longer meets society's needs and expectations. However, issues of fairness, equality, and modern complexities in the division of relationship property are not unique to New Zealand. Other jurisdictions are facing similar problems, including Australia, England and some continental European countries. The inclusion of internationally recognised relationship property experts from England, Australia and Germany ensures the utility of the book for international audiences, making it of interest to law reformers, academics, the judiciary, the legal profession, and law students everywhere in the world.